PELAKSANAAN FARDHU KIFAYAH BAGI JENAZAH BAYI KEGUGURAN (Ahkam: Jurnal Hukum Islam, 2022)
This research is about the implementation of Fardhu Kifayah for the bodies of aborted babies who are over four months old. This type of research is library research, with descriptive analysis characteristics. The problem in this paper is related to the implementation of Fardhu Kifayah for abortion babies, several Mujtahid priests, in this case, the Hanafi, Malik, and Syafi'i priests believe that all Fardhu Kifayah is carried out if there are signs of life or Istihlal, if not, it is sufficient wrapped in cloth and then buried. Meanwhile, Ahmad Bin Hanbal stated that if the baby who miscarried was old enough to be breathed by the spirit, namely four months of pregnancy, all Fardhu Kifayah must be carried out. The difference of opinion of the Imams of this school arises because of differences in determining the limits of a child being categorized as alive, Imam Hanafi, Malik, and Shafi'i determine whether the baby is alive or not at birth, while Imam Ahmad sees the time or even the spirit is blown, namely when the fetus is 120 days old. This paper concludes that Imam Ahmad's opinion is more relevant and provides benefits for the community because it is easier to determine the implementation of the law and avoid new differences of opinion among the community.
Keywords: Fardhu Kifayah; body; Miscarriage Baby